An evidence-based framework for priority clinical research questions for COVID-19 - Harris, C; Carson, G; Baillie, JK; Horby, P; Nair, H (International Society of Global Health, 2020)
Background On 31 December, 2019, the World Health Organization China Country Office was informed of cases of pneumonia of unknown aetiology. Since then, there have been over 75 000 cases globally of the 2019 novel coronavirus (COVID-19), 2000 deaths, and over 14 000 cases recovered. Outbreaks of novel agents represent opportunities for clinical research to inform real-time public health action. In 2018, we conducted a systematic review to identify priority research questions for Severe Acute Respiratory Syndrome-related coronavirus (SARS-CoV) and Middle East Respiratory Syndrome-related coronavirus (MERS-CoV). Here, we review information available on COVID-19 and provide an evidenced-based framework for priority clinical research in the current outbreak.